Study on Morbidity and Mortality Rates in Buffaloes in Pune Division of Maharashtra State in India - Bangar, Y. C.; Khan, T. A.; Dohare, A.; Kolekar, D. V.; Avhad, S. R. (Journal of Buffalo Science, 2014)
The present study was carried out to analyse morbidity and mortality rate in buffaloes and its associated factors in Pune division of Maharashtra state in India. Stratified two stages random sampling design was adopted & the data of total 564 buffaloes were collected through pre-tested modified schedule from 157 buffalo owners. The data were analysed statistically by SAS 9.3 software for evaluation of Chi-square and Logistic regression analysis. Overall morbidity (28.01%) and mortality (7.98%) rates were recorded in study area. Digestive diseases and respiratory diseases are major cause of the higher morbidity and mortality in buffaloes, respectively. Statistically, there wasn’t significant association of overall disease incidence with age or sex. However, the Chi-square analysis of overall mortality rate showed significance (p<0.01) difference among age and sex. Logistic regression analysis also suggested the same results. Mortality rates were recorded higher in calves and male buffaloes as compared to their respective counterparts. It is suggested that digestive and respiratory problems may be reduced by improving feeding and management practices. This study provides the important tool for determining the health status of buffaloes and has special importance in planning of prevention and control strategies designed to reduce the incidences of diseases in livestock and therefore economic status of farmers.